2018
DOI: 10.3892/etm.2018.6454
|View full text |Cite
|
Sign up to set email alerts
|

Applications and development of permeability imaging in ischemic stroke (Review)

Abstract: Abstract. Brain permeability imaging techniques are specific for the assessment of blood-brain barrier integrity. The present review article primarily focuses on the application of permeability imaging in cases of ischemic stroke. The permeability maps may be used to predict future hemorrhagic transformation in patients following acute ischemic stroke, that have been treated with tissue plasminogen activator (tPA) or recanalization therapy. The permeability imaging would help make the clinical decision to admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The resolution of imaging is inferior to that acquired by dynamic contrast enhanced magnetic resonance (MR) imaging (DCE-MRI) scan [ 22 ]. Besides, the extent of BBB damage evaluated by DCE-CT scan may fluctuate depending on the cerebral blood flow, and therefore BBB disruption cannot be detected in severe ischemic region because of the insufficient blood supply [ 20 ].…”
Section: Assessment Of Bbb Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The resolution of imaging is inferior to that acquired by dynamic contrast enhanced magnetic resonance (MR) imaging (DCE-MRI) scan [ 22 ]. Besides, the extent of BBB damage evaluated by DCE-CT scan may fluctuate depending on the cerebral blood flow, and therefore BBB disruption cannot be detected in severe ischemic region because of the insufficient blood supply [ 20 ].…”
Section: Assessment Of Bbb Permeabilitymentioning
confidence: 99%
“…The time-consuming nature may be a critical factor that leads to worse clinical outcomes in patients with acute ischemic or hemorrhagic stroke before intervention. Other limitations include potential artifacts as a major concern, and that this method is still difficult to detect slight BBB injury [ 20 , 225 - 227 ]. In contrast, recent studies showed that arterial spin labeling (ASL) techniques of MRI could be used for evaluation of BBB integrity based on the different diffusion or transverse relaxations by separating the intravascular and extravascular signaling [ 228 ].…”
Section: Assessment Of Bbb Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation